Oral Delivery of miRNA With Lipidic Aminoglycoside Derivatives in the Breastfed Rat - Beuzelin, Diane; Pitard, Bruno; Kaeffer, Bertrand (Frontiers in Physiology, 2019)
Context: Specific targeting of endogenous miRNAs which are involved in epigenetics, may help understanding homeostasis with therapeutic benefits. We use new biologically-inspired vehicles consisting of lipoaminoglycosides to deliver in vivo mir-320-3p, a known human breast milk exosomal miRNA, or its antagomiR. Material &Methods: Four lipoaminoglycosides were screened for cytotoxicity and their biophysical properties. One-hour breast-restricted rats received single-oral treatment of either the lipoaminoglycoside Dioleyl-Succinyl Paromomycin (DOSP) complexed with miRNA or antagomiR, or of control medium at the light on (ZeitGeber Time: ZT-0H) or off (ZT-12H). Glycemia, triglycerides, cholesterol, free-fatty acid were assayed at 0, 4, 8 and 12h post-treatment. In the stomach, small intestine, liver, plasma, adipose tissue, plexus choroid and cortex, relevant miRNA with precursors and mRNA (polr3d, hspb6, c-myc, stat1, clock, bmal1, per1, npas2, sirt1-6, cyclinD1) were quantified by q-PCR. Expression of POLR3D and HSPB6 proteins were analyzed in stomach and liver by Western blot. Immunoprecipitations with anti-AGO1 and 2 were performed on nuclear and cytoplasmic fractions of gastric cells along with detection of miRNA-320-3p in nucleoli. Chromatin ImmunoPrecipitation with anti-Trimethyl-histone-3-Lys-4 and Lys-27 detecting the polr3d promoter and miR-320-3p, were performed for all groups. Results: Selected DOSP (diameter: 80-200 nm) did not alter gastric extracellular vesicle secretion a few hours after intake. The miR-320-3p was mainly found in gastric or small intestinal cells, reaching the blood and liver in low amount. We have found significant up-regulation of polr3d mRNA (ANOVA p<0.0001) at ZT-20H for the miR-320-3p-supplemented group and a higher expression of POLR3D for antagomiR group (ANOVA p<0.05). We had a low accumulation of miR-320-3p at ZT-20H in nucleoli, without evolution of stat1. Delivering a high amount of miRNA or antagomiR disrupts RNA-Induced Silencing Complexes in cytoplasm triggering some transfer of extracellular molecules into nuclei with alteration of immune complexes on the polr3d promoter (with a higher amount found in the K4 histone-3-me3 immune complexes at ZT-20H). Conclusion: Extracellular miRNAs embedded in DOSP have a rapid impact on RNAi and on nuclear chromatin complexes depending on the daily rhythm. An integrative view of the impact of extracellular miRNA on physiology will improve assaying epigenetic manipulations following nutritional stress.